Overpressures Induced by Compaction Disequilibrium Within Structural Compartments of Murree Formation, Eastern Potwar, Pakistan - Amjad, Muhammad Raiees; Zafar, Muhammad; Ahmad, Tausif; Hussain, Muyyassar; Shakir, Urooj (Frontiers in Earth Science, 2022)
Overpressure conditions in Potwar Basin of Pakistan pose significant drilling and completion problems. Specifically, in eastern Potwar, abnormally high pressures are observed within structural compartments of Murree Formation of Neogene age. Compaction disequilibrium and tectonic stresses are considered as two major factors, controlling pore pressures in this foreland basin. Undercompaction of sediments due to high sediment influx affects the porosity-depth relationship as the rock deviates from the normal compaction trend. Demarcation of structural geometries is critical in understanding abnormal pressure conditions within thick molasse deposits of Murree Formation. Eastern Potwar is divided into three zones on the basis of structural geometries, including duplex thrust sheets, salt-cored anticlines, and triangular zones. Geohistory analysis and pore pressure prediction have been performed for determining the overpressuring mechanism. Log-based pressure prediction in different oil fields of eastern Potwar depicts anomalous pressure conditions in some of the wells. High-sedimentation rate during Miocene times resulted in a low porosity reduction rate due to the inability of fluid to escape out of the pores. Eaton’s method was used to predict the pore pressure, and these pressure curves were calibrated against measured pressure to validate the results. Pressures predicted in Qazian-1X well showed very good correlation with measured pressure data. Most of the wells with overpressure intervals exhibited high porosity values, showing deviation from the normal compaction trend. This pressure prediction revealed that compaction disequilibrium is the primary cause of overpressure conditions within Murree Formation, resulted in response to the rapid rate of sedimentation. The deformation mechanism and presence of different structural geometries also contributed in the development of abnormal pressures.